Artistic Interpretation of Alisher Navoi’s Image in Uzbek Literature of the Independence Period - Ashurova, Gulbahor (International Journal of Psychosocial Rehabilitation, 2020)
The interest in Navoi’s work, the study and analysis of his works is a continuous process that has been going on since the time of the thinker-poet. Navoi’s work is such a vast ocean that every generation can collect its own jewels. Realizing Navoi is equal to knowing the history, culture, national identity and soul of Uzbek nation. Today, one of the main tasks of the society is to bring up young people with high human qualities, and in this process, the works of Alisher Navoi will serve as an invaluable source. Not only his works, but also the exemplary way of life of this great figure, the image of which has become a symbol of perfection, is a real guiding star for our contemporaries.